Special Needs and Tertiary Institutions Educational Goal Achievements in Universities in Kwara State (Kwasu International Journal of Educational Management and Leadership, 2026)
Education is designed to equip the citizens with the needed knowledge and skills to contribute to national development and students with special needs are not expected to be left out, hence, the study investigated the special needs education and the achievement of tertiary educational goals in Kwara State. The study adopted a descriptive research of the survey type. A sample of 200 respondents were selected for the study, a researcher-designed questionnaire was used to elicit data. Descriptive survey design was used for this study. The findings of the study, among others, revealed that there was a significant relationship between special needs education and tertiary institutions educational goals achievements in Kwara State. Based on the findings of the study, the study concludes that greater awareness programmes is paramount in order to provide a pathway for improving inclusivity and accessibility. It was recommended that institutions should invest in modern educational infrastructure, faculty training, and student support programmes to improve overall educational goal achievement; Universities should integrate inclusive curricula, expand disability support services, and establish partnerships with organizations specialising in special needs education.